2012
DOI: 10.1128/mcb.06595-11
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO Pathway Promotes Basic Helix-Loop-Helix Proneural Factor Activity via a Direct Effect on the Zn Finger Protein Senseless

Abstract: bDuring development, proneural transcription factors of the basic helix-loop-helix (bHLH) family are required to commit cells to a neural fate. In Drosophila neurogenesis, a key mechanism promoting sense organ precursor (SOP) fate is the synergy between proneural factors and their coactivator Senseless in transcriptional activation of target genes. Here we present evidence that posttranslational modification by SUMO enhances this synergy via an effect on Senseless protein. We show that Senseless is a direct ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Most importantly, E(spl) proteins also interact with a StUbl (SUMO-targeted ubiquitin ligase), called Degringolade, and their ubiquitylation seems to decrease their affinity for Gro Barry et al, 2011;Powell et al, 2012). Thanks to their duplication, Drosophila E(spl) can form many homo-and heterodimers with differential affinities for Da, Sc, Ato, and probably other proneural proteins; these preferences are partly mediated by their Orange domains.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Most importantly, E(spl) proteins also interact with a StUbl (SUMO-targeted ubiquitin ligase), called Degringolade, and their ubiquitylation seems to decrease their affinity for Gro Barry et al, 2011;Powell et al, 2012). Thanks to their duplication, Drosophila E(spl) can form many homo-and heterodimers with differential affinities for Da, Sc, Ato, and probably other proneural proteins; these preferences are partly mediated by their Orange domains.…”
Section: Closing Remarksmentioning
confidence: 99%
“…2). Sens directly binds to proneural proteins, including Atonal, via its Zn-finger domains (24,(64)(65)(66). This interaction enhances the activity of the bHLH factor at its target genes.…”
Section: How Might Atoh1 and Gfi1 Interact?mentioning
confidence: 99%
“…Gfi1 protein contains a SNAG domain which recruits co-repressors (Velinder et al 2016;Zweidler-Mckay et al 1996;Grimes et al 1996), and it acts as a major transcriptional repressor during haematopoiesis (Möröy et al 2015;Möröy and Khandanpour 2011;van der Meer et al 2010). However, the Drosophila orthologue of Gfi1 (Senseless, SENS) (Nolo et al 2000) has been reported to have dual functionality: SENS can act as a DNA-binding transcriptional repressor but also as a transcriptional co-activator of proneural TFs (including Atonal), enhancing their ability to stimulate sensory gene expression (Acar et al 2006;Jafar-Nejad et al 2003a;Powell et al 2008;2012b). Our observation of two distinct populations of Gfi1 sites in iHCs suggests that Gfi1 may similarly have dual functionality.…”
Section: Gfi1 Regulates Hc Differentiation Through Both Repression Anmentioning
confidence: 81%